2010
DOI: 10.1111/j.1467-9221.2010.00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Challenging the Stubborn Core of Opposition to Equality: Racial Contact and Policy Attitudes

Abstract: A Random Digit Dialing survey (n = 794) examined the interracial contact experiences and racial attitudes of White South Africans. The survey measured racial attitudes not only in terms of individuals' prejudice, but also in terms of their perceptions of group threat, perceived injustice, and support for various government policies designed to rectify the legacy of apartheid. The results indicated that the frequency and quality of interracial contact predicted Whites' support for both race compensatory and rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 55 publications
2
70
0
2
Order By: Relevance
“…The clearest finding of this study is that general contact with members of racial outgroups is associated with lower levels of reported prejudice. This finding contributes to the contact literature in South Africa and supports the growing consensus that increased contact is generally an effective means of reducing prejudice (Finchilescu & Tredoux, 2008;Dixon et al, 2010;Gibson & Claassen, 2010;Swart et al, 2010; Despite the small sample size, direct contact with multiracial families had a significant relationship with prejudice over and above the effects of general contact. Although extended contact with multiracial families predicted reduced prejudice by itself, it did not retain significance when direct contact with multiracial families and general contact were entered into the model and it was not possible to explore the independent effect of extended contact with multiracial families on prejudice due to the substantial overlap between measures.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The clearest finding of this study is that general contact with members of racial outgroups is associated with lower levels of reported prejudice. This finding contributes to the contact literature in South Africa and supports the growing consensus that increased contact is generally an effective means of reducing prejudice (Finchilescu & Tredoux, 2008;Dixon et al, 2010;Gibson & Claassen, 2010;Swart et al, 2010; Despite the small sample size, direct contact with multiracial families had a significant relationship with prejudice over and above the effects of general contact. Although extended contact with multiracial families predicted reduced prejudice by itself, it did not retain significance when direct contact with multiracial families and general contact were entered into the model and it was not possible to explore the independent effect of extended contact with multiracial families on prejudice due to the substantial overlap between measures.…”
Section: Discussionsupporting
confidence: 82%
“…Race policy attitudes were operationalized as support for government policies designed to rectify race-based injustices in education, housing, land reforms and jobs using scales from Durrheim et al Dixon et al (2010). These items scaled with excellent reliability ( a = .899).…”
Section: Assessing Race-policy Attitudesmentioning
confidence: 99%
“…As noted, Durrheim's article (this issue) reported this phenomenon. And another South African survey obtained the strongest evidence yet obtained of intergroup contact shaping policy preferences (Dixon, Tredoux, et al, in press). A random digit dialing telephone survey of South Africans found that both the frequency and quality of interracial contact related positively to White support for both racial compensatory and racial preferential policies of redress.…”
Section: Intergroup Contact In the New South Africamentioning
confidence: 99%
“…In turn, this process is assumed to gradually erode inequality at a collective and institutional level. Closely related, by decreasing the likelihood that the historically advantaged will act in ways that defend their privileges, prejudice reduction also undermines the so-called stubborn core of resistance to social change at a societal scale (Dixon et al, 2010a). It weakens, for instance, resistance to policies such as affirmative action, educational quotas, and increased taxation of the rich.…”
Section: Prejudice Reductionmentioning
confidence: 99%